Pelatihan Manajemen Keuangan Pribadi untuk Pelajar di SMA Negeri 1 Sungai Rotan - Maryani, Maryani; Nurfatidah, Sri (Jurnal Nasional Pengabdian Masyarakat, 2024)
Personal financial management in a student environment is an important aspect in forming good financial skills at an early age. This research aims to explore the application of personal financial management among students, assess their understanding of financial management, and identify challenges faced in daily practice. Issues raised include a lack of formal financial education, a lack of knowledge of budgeting, and unhealthy spending habits. The method used is descriptive qualitative, involving students from various classes and new students at tertiary institutions. Data was collected through a questionnaire designed to measure understanding and practice of personal financial management. It is hoped that the results of this research will provide useful insights for students and educational institutions in designing more effective financial education programs and helping students develop healthy financial habits. By implementing proper financial management, students are expected to be able to avoid financial problems in the future and become more financially independent individuals.